Botulinumtoxin in der Augenheilkunde = Botulinumtoxin in ophthalmology - Wabbels, Bettina Kathrin (Klinische Monatsblätter für Augenheilkunde, 2019)
Botulinum toxin has been first applied in ophthalmology (as treatment for strabismus) and is nowadays widely used in many clinical areas. Currently the main application in ophthalmology is the treatment of essential blepharospasm and hemifacial spasm. Other important indications for botulinum toxin in ophthalmology are eyelid retraction in Gravesʼ disease and the induction of protective ptosis in lagophthalmos or corneal diseases.